Proposed Crane Machine Maintenance Schedule with Reliability Centered Maintenance Method: Usulan Jadwal Pemeliharaan Mesin Crane Dengan Metode Reliability Centered Maintenance - Pratama, Dimas Maulana Agta; Widiasih, Wiwin (Universitas Muhammadiyah Sidoarjo, 2024)
PT XYZ is a steel smelting company located in Sidoarjo. The company is assisted in the production process by a total of 15 cranes to lift loads that cannot be lifted by bare human hands. Currently the crane machine has the highest downtime of 157 hours compared to other machines. The components that are often damaged are the hover control, braking system, and trolley cable. The purpose of this research is to find out what causes high downtime, know the maintenance schedule, and can improve the reliability of critical components. This research will discuss the maintenance scheduling of crane machine No. 5 using the Reliabilty Centered Maintenance method. The results showed that the cause of high downtime is 3 critical components, namely hover control, braking system, and trolley cable. The proposed maintenance schedule for the 3 critical components has a maintenance time interval of hover control every 250 hours, braking system every 397 hours, trolley cable every 1460 hours, and the machine reliability obtained is 60%. The costs incurred for preventive maintenance amounted to Rp. 382,104,000, this figure increased by Rp. 185,840,000 from the cost of corrective maintenance which initially amounted to Rp. 196,264,000.